Augustine and his critics : essays in honour of Gerald Bonner - Bonner, Gerald; Dodaro, Robert, 1955-; Lawless, George (London ; New York : Routledge, 2000)
Augustine of Hippo (AD 354-430) is arguably the most controversial Christian thinker in history. His positions on philosophical and theological concerns have been the subjects of intense scrutiny and criticism from his lifetime to the present. Augustine and his Critics gathers twelve specialists' responses to modern criticisms of his thought, covering: personal and religious freedom; the self and God; sexuality, gender and the body; spirituality; asceticism; cultural studies; and politics. Stimulating and insightful, the collection offers forceful arguments for neglected histori.
Gerald Bonner: an appreciation / Daniel W. Hardy -- Gerald Bonner: a select bibliography / Daniel W. Hardy -- Studying Augustine: an overview of recent research / Hubertus R. Drobner -- Paucius mutatis verbis: St Augustine's Platonism / Robert Crouse -- The fundamental grammar of Augustine's trinitarian theology / Lewis Ayres -- Sacred triads: Augustine and the Indo-European soul / John Milbank -- Insubstantial evil / Rowan Williams -- Snares of truth: Augustine on free will and predestination / James Wetzel -- Augustine's decentring of asceticism / George Lawless -- Christ, God and women in the thought of St. Augustine / E. Ann Matter -- A critical evaluation of critiques of Augustine's view of sexuality / Mathijs Lambertigts -- 'Tempora christiana' revisited / Robert A. Markus -- The rhetoric of scripture and preaching: classical decadence of Christian aesthetic? / Carol Harrison -- Augustine's secular city / Robert Dodaro.
"Gerald Bonner: a select bibliography": pages 11-17
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustin, -- saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Electronic books; Festschriften; Festschriften